ETNISITAS DALAM POLITIK (STUDI TENTANG STRATEGI CALON LEGISLATIF ETNIS BATAK DALAM PEMILIHAN UMUM LEGISLATIF DI DAERAH PEMILIHAN SIAK 4 KABUPATEN SIAK TAHUN 2014) - Zuhar, Ammar; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to see the victory of the Batak ethnic candidates in legislative elections in the electoral district Siak 4 on 2014 and the focus of this research is how the political strategy of the Batak ethnic candidates in the legislative elections unum. Besides that are the focus of this research was the influence of ethnic communities in the Batak winning candidates in the electoral district Siak 4 on the Siak district legislative elections in 2014. In this research, using qualitative methods, then to describe the data presented in the form of qualitative describe the real situation in detail and the actual look at the problem and research objectives. This research using purposive sampling and interviewing informants as objects of information that aims to achieve the purpose of obtaining information in the study. The type of data used in this research are primary and secondaryThe results showed in pursuing a strategy undertaken by candidates Batak in legislative elections in the constituency Siak 4 on 2014, there are several strategies undertaken by candidates Batak ethnic like using the communication strategy of groups, communication between individuals and the use of media outside. Role Batak ethnic communities so strongly that a strategy candidates utilizing ethnic Batak in legislative elections in the electoral district in Siak 4 on 2014. So that the ethnic Batak utilization strategy undertaken by candidates of ethnic BatakKey Words: Politic Strategic, Legislative Election, Batak Etnic